2013
DOI: 10.1016/j.neuroscience.2013.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Motor stereotypies and cognitive perseveration in non-human primates exposed to early gestational irradiation

Abstract: A number of psychiatric illnesses have been associated with prenatal disturbance of brain development, including autism, attention deficit hyperactivity disorder, and schizophrenia. Individuals afflicted with these disorders exhibit both repetitive motor and cognitive behavior. The potential role that environmental insult to the developing brain may play in generating these aberrant behaviors is unclear. Here we examine the behavioral consequences of an early gestational insult in the non-human primate. Rhesus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 68 publications
1
4
0
2
Order By: Relevance
“…The broadest performance difference between the two groups was demonstrated at the re-reversal phase, which suggests that the control animals learned to adapt to the task’s changing rules while the irradiated animals lacked the cognitive flexibility necessary to do so. Similar increased perseverative errors were reported in a study of juvenile and adult macaques that were exposed to radiation in utero (39). In addition, survivors of pediatric cranial lymphoid malignancies showed deficits in cognitive flexibility 25 years after receiving radiotherapy (35).…”
Section: Discussionsupporting
confidence: 83%
“…The broadest performance difference between the two groups was demonstrated at the re-reversal phase, which suggests that the control animals learned to adapt to the task’s changing rules while the irradiated animals lacked the cognitive flexibility necessary to do so. Similar increased perseverative errors were reported in a study of juvenile and adult macaques that were exposed to radiation in utero (39). In addition, survivors of pediatric cranial lymphoid malignancies showed deficits in cognitive flexibility 25 years after receiving radiotherapy (35).…”
Section: Discussionsupporting
confidence: 83%
“…Previous research indicated that behavioural defects after in utero radiation exposure highly depend upon the evident morphological changes, such as brain volume decrease, ventricular enlargement and cortical thinning [ 71 ]. This is further evidenced in non-human primates, in which morphological effects induced by prenatal radiation exposure are thought to be responsible for neurological symptoms [ 72 , 73 ]. Here, we observed both abnormalities in neurogenesis as well as morphological aberrations.…”
Section: Discussionmentioning
confidence: 99%
“… 8 As adults, fetally irradiated monkeys exhibit motor stereotypies, cognitive perseveration and profound working memory deficits, indicating that the prefrontal cortical and corticostriatal loop functions are impaired by fetal exposure to irradiation. 102 , 103 Most intriguingly, the same fetally irradiated animals that exhibit severe cognitive deficits and motor stereotypies as adults were indistinguishable from their normal counterparts as juveniles. 102 , 103 These observations indicate that the ‘lesion' incurred by fetal irradiation in the prefrontal cortex remains dormant and is expressed only as the animals mature to adulthood, perhaps when late adolescent developmental processes unmask the underlying ‘lesion.'…”
Section: Cell Proliferation: a Vulnerable Developmental Process In Eamentioning
confidence: 99%